Effects of Internal Controls in the Detection of Frauds in Public Institutions a Case Study of the University of Embu - Nyawira, Fidelis Veronica (University of Embu, 2019)
There has been a rise in the cases of fraud in the public institutions and in some the occurrence of this issue becomes repeated like in the case of NYS. In the fraud issues some of the top management employees have been pointed out as part of the involved personnel in the fraudulent practices. Although various internal controls have been put in place to prevent fraud from occurring, the institutions do not enforce them as required. Also the cases of frauds are not stopped before occurring or coming to the public eye since the public institutions have not invested much in detective controls and any fraud issues can only get detected when fraud has already occurred over a period of time. If any detective controls have been put in place they are not enforced and hence personnel can easily manipulate them and find a way around them. These cases of increased fraudulent cases in public institutions formed the basis for the study. This study will use University of Embu as the center of the case study to examine how public institutions have invested in the controls. The study put to use the explanatory research design. The population of the study included personnel from finance and accounting department and the sample was drawn from the various subdivisions in the department. The sample will be determined through judgmental sampling. The study used primary data by use of questionnaire. Multiple linear regression was used in data analysis.